Long-term clinical evaluation of the color stability and stainability of acrylic resin denture teeth - Ricardo Barao, Valentim Adelino; Ogawa, Erika Shiguematsu; Moreno, Amalia; Mesquita, Marcelo Ferraz; Wee, Alvin G.; Assuncao, Wirley Goncalves [UNESP] (Elsevier B.V., 2015)
Statement of problem: The color stability and staining of acrylic resin denture teeth remains an esthetic problem for complete denture wearers. Purpose: The purpose of this study was to evaluate the long-term clinical color stability and stainability of acrylic resin denture teeth in complete denture wearers over a period of 5 years. Material and methods: Fifty participants rehabilitated with complete dentures from February 2008 to December 2013 were selected. The demographic data and the clinical characteristics of participants were recorded. Color change (Delta E) in 3 regions of the denture teeth (incisal, middle, and cervical) was evaluated by spectrophotometry in the CIE L*a*b* system. Participants were asked whether they had noticed any changes in the coloring of the teeth in their dentures. Hierarchical clustering analysis was used to identify groups formed from variables related to demographic questions and color analysis. Two-way ANOVA among the color cluster groups was performed and the Tukey-Kramer test was used as a post hoc test (alpha=.05). A chi-square test and Fisher exact test were used to identify the association between the study variables and color changes in the participants'responses (alpha=.05). Results: Four cluster groups from 50 participants were identified in the clustering analysis. The Delta E was statistically significant for the interaction between the dental third and cluster groups (P < .001). Cluster groups 1 and 4 exhibited statistically higher Delta E values than cluster groups 2 and 3 (P < .05). Greater chromatic alterations were noted in the incisal third of the teeth than in the cervical and medium thirds in the cluster groups 1 (Delta E=11.03 +/- 1.22) and 3 (Delta E=4.14 +/- 1.14) (P < .05). No relationship was found with the participants'personal opinions about color change (P > .05). Conclusion: Although the acrylic resin denture teeth exhibited color instability and staining in vivo, the participants were unable to identify the color change. The cluster groups with higher color change values consumed more staining solutions.